Study of Perception and Attitude towards Eco-Friendly Concerns of Indonesian Cosmetics Consumers - Soerjanatamihardja, Karissa Adhyaningrum; Fachira, Ira (Journal of Business and Management, 2017)
Abstract.Background: In Indonesia, the demand for cosmetics is soon to arise further over the coming years. Claims are that there has been an average annual increase of 9.67% of the years 2010-2015. A global phenomenon in business also has shown that cosmetics companies are shifting towards green movement and sustainability. 64% of Indonesian consumers are said to be prepared to spend extra for products and services that come from companies that represent eco-friendly practices.Methods:  An online questionnaire was distributed to 384 respondents, all female inhabitants of Jakarta and Bandung between the ages 16-50, by non-probability purposive sampling. The data was analyzed using factor analysis, multiple linear regression, MANOVA and cluster analyses.Results:  Perceived importance of green corporate practices and green marketing mix has influence towards attitude towards green values. A six cluster-solution was identified by variables influenced by Ottman’s deep-green sub-segments and attitude towards green values.Conclusion: This study focuses mainly on perceived importance and attitude towards green marketing of cosmetics consumers in Indonesia, providing information of segmentation, perception and attitude to impact businesses embarking green marketing as the holistic concept of their business processes. Keywords: Cosmetics, Consumer Attitude, Consumer Perception, Green Marketing, Ottman’s Deep Green Sub-Segments